Abu Bakar and the Singapore authority: The colonial trajectory of economic dependency - A Rahman Tang Abdullah (Faculty of Arts and Social Sciences, University of Malaya, 2010)
This article discusses the importance of Johor's economic dependence on the British in Singapore as a means of preserving the internal independence of Johor during the reign of Abu Bakar. It re-examines the general consensus among historians who credit Abu Bakar's distinctive reputation as the main reason for his ability to resist British intrusion into Johor despite the state's proximity to Singapore the seat of power of British imperialism in Southeast Asia. This general consensus is subjected to further examination as it suggests that relations between Johor and the British in Singapore were extensively preoccupied by political rather than economic issues. In reality, economic imperialism actually preceded political imperialism or colonial expansion. It is evident that the British authority as a whole was more concerned with the economic aspects as the main criteria in formulating their policy towards the Malay states. Hence, it is argued here that Johor was allowed to retain its internal independence as long as it became an economic dependency of the British in Singapore.